Association between trans-palmitoleic acid and metabolic dysfunction-associated steatotic liver disease-related hepatocellular carcinoma: NHANES 1999–2018 - Li, Qirui; Zhan, Luqi; Li, Qian; Zhu, Shuai; Liu, Shuaihui; Jiang, He; Cheng, Jinlin; Li, Lanjuan (Frontiers in Nutrition, 2025)
IntroductionMetabolic dysfunction-associated steatotic liver disease (MASLD) is a global health burden with an increasing incidence of hepatocellular carcinoma (HCC), yet early risk predictors remain elusive. This study investigated trans-palmitoleic acid (TPA) as a potential biomarker for MASLD-HCC risk.MethodsUsing National Health and Nutrition Examination Survey (NHANES) data (n = 548), propensity score matching (PSM) minimized sociobehavioral confounders. Multivariable logistic regression and restricted cubic spline (RCS) models were employed to assess the association between TPA and HCC risk.ResultsA striking nonlinear association between TPA and HCC risk was observed (P-nonlinear <0.001). Each unit increase in TPA elevated HCC risk by 52.4% (OR = 1.524, 95% CI = 1.397–1.677), with quartile analysis showing exponential risk escalation (Q4 OR = 753.7). Subgroup analyses identified heightened susceptibility in women (Q4 OR = 1148.83) and younger individuals (OR = 612.11). TPA correlated positively with lipid factors (triglycerides β = 1.236, LDL β = 0.557) and hematologic indices, while exhibiting a negative association with BMI (β = −0.037). Mediation analysis implicated triglycerides as a key metabolic intermediary (39.18% effect proportion).DiscussionThese findings establish TPA as an independent MASLD-HCC risk factor with distinct demographic variability, potentially mediated through lipid dysregulation. While limited by observational design, this study highlights TPA’s prognostic value for HCC risk stratification, especially in non-diabetic populations (OR = 257.14). Future mechanistic studies should validate TPA’s oncogenic pathways and explore therapeutic targeting of trans-fatty acid metabolism to mitigate MASLD progression. The robust dose-response relationship and metabolic mediation effects position TPA as a promising candidate for incorporation into existing HCC prediction models.